Characterization of a novel algicidal bacteria Arenibacter sp. strain 6A1 and its application to eliminate harmful algal blooms - Wu, Sha; Tong, Jing; Chen, Jiahuan; Chen, Minchun; Wang, Liyan; Li, Shuangfei; Hu, Zhangli; Chen, Huirong (Frontiers in Marine Science, 2024)
Hazardous impacts caused by harmful algal blooms (HABs) have facilitated the development of novel effective approaches for controlling the frequent HABs. Recently, bacteria with algicidal effects, as a promising alternative tool for eliminating the HABs-forming species have received wide concerns. In the present study, a marine bacterial strain 6A1 with potent algicidal activity was successfully isolated from a bloom of Akashiwo sanguinea, and the characteristics related to its algicidal action were systematically investigated. Sequencing results of 16S rDNA suggested that this bacterium belongs to the genus Arenibacter in the family Flavobacteriaceae, while the phylogenetic analysis revealed that Arenibacter sp. strain 6A1 was the only algicidal bacterium in Arenibacter to date, according to the best of our knowledge. Arenibacter sp. strain 6A1 had an extraordinarily high algicidal performance when it was added to A. sanguinea culture with a volume fraction of 1.5% for 2 h. The algicidal performance of strain 6A1 was concentration-dependent and time-dependent. The best algicidal efficacy of strain 6A1 was seen during the stationary phase, while the resistance of A. sanguinea to strain 6A1 declined as the growth cycle progressed. Subsequently, the indirect algicidal mode of Arenibacter sp. strain 6A1 was verified and the algicidal compounds produced by strain 6A1 were proved to be heat-resistant. Further research showed that strain 6A1 caused a severe damage in photosynthesis, oxidative stress, and also damage in three HABs-forming algae to varying degrees. The greatest algicidal performance was found on unarmored dinoflagellate A. sanguinea, followed by raphidophyte Chattonella antiqua and armored dinoflagellate Alexandrium tamarense. The Arenibacter sp. strain 6A1 exhibited selective algicidal activity on a wide range of algal species, primarily targeting Pyrrophyta and Ochrophyta. The proposed bacteria (strain 6A1) can be a powerful and eco-friendly tool for emergency treatment of HABs caused by certain algal species in coastal water bodies.